Composition portfolio - Wynne, Donovan (Rhodes University, Faculty of Humanities, Department of Music and Musicology, 2006)
Introductory remarks: Being a middle-class white South African, I grew up on a diet of predominantly "white" music: rock, pop and Western classical music. I was later introduced to a broader range of musics: blues, jazz, kwaito and traditional Southern African idioms. I found myself particularly attracted to the traditional music of the amaXhosa (especially that of the uhadi bow), possibly due to the fact that this music is hexatonic (that is, based on two major triads whose tonics are one tone apart), a system that bears certain resemblances to the Western tonal idiom. However, much of my musical experience tended to be entrenched in the piano and flute music I played: mostly works by composers who were neatly ensconced in the traditional Western canon. Therefore, despite the broad range of musics with which I was familiarisedduring my tertiary studies, I feel that this early experiential background is the reason I feel most comfortable with Western-influenced music. More recently, I discovered a whole new genre to explore: film music, particularly the work of Elliot Goldenthal, Danny Elfman, John Williams and Philip Glass, whose unique brand of minimalism has extended from the concert hall to thefilm theatre. I am fascinated by the ways in which film scores function. A "main titles" theme usually appears as the film opens, upon which most of the subsequent music is based. This is not a linear process, like a theme and its variations, but a lateral, where the main titles theme is the core that engenders other themes that all share a familial resemblance.
Keywords: Music -- South Africa; Composition (Music); String quartets -- Scores